Movable bridge design - Birnstiel, Charles; Bowden, William; Foerster, George A. (ICE Publishing, 2015)
'Movable Bridge Design' provides a fascinating and comprehensive guide to both past and current approaches to the design of a wide range of movable bridges. Against the background of worldwide development, the authors provide the necessary information on the electromechanical and hydraulic systems that drive movable bridges.